The growth of government spending in Algeria during the period (1969-2014)Between Wagner’s Law and the Keynes hypothesis - boulkour, Noureddine (Dirassat Journal Economic Issue, 2016)
This study aims at the relationship between government spending (EXP) and gross domestic product (GDP) in Algeria during the analysis period (1969ــــ 2014) in the short term and long term, for it was used as a test standard methods of modern time series Yeh stability and integration in a manner common Engle and Granger model error correction and Granger causality. This study concluded that the GDP and government spending characterized feature unionist roots and they are on a common complementary relationship, and that there is a causal relationship of short and long-term trending of GDP to government spending, reflecting the health of the Wagner Act in the Algerian economy.